Technical Analysis of The Use of Shore Connection Services at Tanker Docks - Zapata, Malvin; Prayogi, Soni (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2024)
The use of shore connection services at tanker berths is an important innovation to increase energy efficiency and reduce greenhouse gas emissions in the maritime sector. This research analyzes the technical aspects of implementing shore connections, including system configuration, integration with port infrastructure, as well as operational and economic challenges. This study uses a descriptive analysis method with data collected through field observations, interviews with port operators, and a review of related literature. The research results show that the implementation of shore connections is able to reduce fuel consumption and pollutant emissions significantly. However, there are obstacles such as high initial investment costs, the need for international technical standards, and adjustments to ship operations. Recommendations include increasing cooperation between ports and shipowners, as well as developing incentive policies to encourage the adoption of this technology. This research provides valuable insights for stakeholders in efforts to achieve more sustainable shipping.